In Memoriam – Professor Czesław LEWA - Antoni ŚLIWIŃSKI; Bogumił LINDE (Archives of Acoustics, 2016)
Professor Czesław Lewa – retired professor of the University of Gdansk passed away after his long illness on the 9th of August 2016.